RECONSTRUCTION OF CRIMINAL SANCTIONS PENAL CODE ACTORS ON ABORTION CRIME BASED ON THE VALUE OF JUSTICE - Hanuring Ayu Ardhani Putri; Teguh Prasetyo; Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Life is a gift given by God Almighty that must be respected by everyone. Life is given to every human being is a human rights that can only be revoked by the Giver of life. The right to life is one of the human rights that are set out in the Constitution of the State, as described in Article 28 (a) of the Constitution of the Republic of Indonesia in 1945 which states that "Everyone has the right to live and to defend life and living". With the right to life of the country will preserve and protect the right to life of every citizen so that the state through the state law enforcement tool will act if there is known to occur and the removal of the right to human life. Abortion (abortion) is always a conversation, either in forumresmi and unofficial concerning the fields of medicine, law and other disciplines. Abortion is not a new issue, abortion is an old problem that is always controversy. One of the controversies about abortion are the priority discourse of human rights as an excuse or reason for the pro-abortion cons of abortion. Lately case of abortion the fruit simalakama in Indonesia. On the other hand nonmedical abortion with reason is strictly prohibited in Indonesia but on the other side of illegal abortions increase the risk of death due to lack of medical facilities and infrastructure, even illegal abortions mostly done by traditional means which increase the risk of death. In Indonesia alone, although abortion is prohibited, but still many women who have abortions. Well done based on specific medical indication or performed by non-medical indications. Experts religion sees that whatever the reason, abortion is an act contrary to the religion, because it is taking the life of the fetus, which means murder, though no one argues that the life of the fetus did not exist before 90 days. Based on consideration of moral and social side, it's hard to let a mother who must care for unwanted pregnancies mainly as a result of rape, the result of commercial sex (with commercial sex workers) and women who know that the fetus has severe physical disabilities. Children born in the conditions and environment such that, in the future will most likely be knocked out of the social life is normal, lack of protection and affection that should be obtained by a child who had grown up in an environment that is fair, so it was likely the child will an outcast. On the other hand, in terms of religion, any religion would not allow men to commit acts termination of pregnancy for any reason, while in terms of the law, there are still debates and contradictions of the pros and cons about the perception or understanding of the laws that exist to date. Today many women became pregnant and had an abortion as a sign of moral degradation. Unwanted pregnancy is not a reason to kill the fetus. The fetus is a creature of Allah SWT. Why should be killed? What is wrong is not a rapist penzinanya or her fetus. The fetus also has the right to life. Legalize abortion is not the solution to reduce the number of maternal deaths. The amount will actually increase because there is the possibility of fetal owner claimed to be raped in order to be aborted. In consideration of hunger, abortion is permitted with some conditions. First, the fetus was detected suffering from a genetic defect that is born later is difficult to cure. Then, pregnancy due to rape were determined by a team competent in it, among others, the victim, a team of doctors and scholars. Terms of abortion due to rape, the age of the fetus can not be longer than 40 days. Criminal punishment against criminal abortion should be through the criminal justice procedure as formal criminal law or the law of criminal procedure. Criminal procedure law that can be formulated as a law establishing how the state uses its right to carry out criminal. Also commonly referred to as Concreto In criminal law, since it contains the rules of how the criminal law or criminal law materiel In Abstracto poured in reality. As known, the setting is a criminal offense in the Criminal Code a criminal abortion contained in the Penal Code Book II Chapter XIV On Crimes Against Life, in Article 299, Article 346, Article 347, Article 348, Article 349. To simplify and ease in this study, the focus directed primarily to the criminal sanctions to abortion.